Effects of Bumblebee Domestication on Pollen Collection - Burtt, Carolyn N. (Tufts University. Tisch Library., 2018)
Summer Scholars 2018 final poster presentation Research with Dr. Elizabeth Crone and her laboratory on the possible link between domestication of Bombus impatiens bumblebees and pollen collection behavior. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.